2020
DOI: 10.3390/cancers12092521
|View full text |Cite
|
Sign up to set email alerts
|

Incidences of Deep Molecular Responses and Treatment-Free Remission in de Novo CP-CML Patients

Abstract: Background: Tyrosine Kinase Inhibitors (TKIs) discontinuation in patients who had achieved a deep molecular response (DMR) offer now the opportunity of prolonged treatment-free remission (TFR). Patients and Methods: Aims of this study were to evaluate the proportion of de novo chronic-phase chronic myeloid leukemia (CP-CML) patients who achieved a sustained DMR and to identify predictive factors of DMR and molecular recurrence-free survival (MRFS) after TKI discontinuation. Results: Over a period of 10 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
2
8
0
1
Order By: Relevance
“…In summary, our results from a population‐based study show that TKI discontinuation in CML in clinical practice is common and feasible and as successful as when performed within a clinical trial. Our findings are also in line with previous reports of discontinuation of TKI therapy in clinical routine that patients treated with second‐generation TKI achieve a higher TFR rate 19,27 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In summary, our results from a population‐based study show that TKI discontinuation in CML in clinical practice is common and feasible and as successful as when performed within a clinical trial. Our findings are also in line with previous reports of discontinuation of TKI therapy in clinical routine that patients treated with second‐generation TKI achieve a higher TFR rate 19,27 …”
Section: Discussionsupporting
confidence: 92%
“…However, basing the estimation on cumulative incidences of DMR tends to overestimate the proportion in stable DMR. In a recent French study of patients treated with TKI outside of clinical trials, cumulative incidence of MR4.0 was 72%, while sustained MR4.0 was reached by 46% after a median follow‐up time of seven years 27 . In addition, a prerequisite for reaching this optimal TFR rate is a consensus between individual patients and treating physicians that TFR is the goal of the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline characteristics of the study population have been previously reported 13 . Briefly, the median age at diagnosis was 61.7 years (range, 18.6 to 90.2 years), 58% of patients were male, and Sokal and ELTS risk scores were high in 19% and 13% of them, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the hypothesis that first‐line TKI type (IMA vs 2‐3G TKI) may have an impact on MRFS, 13 we next analyzed the impact of first‐line TKI together with the selection criteria proposed by recommendations. None of the 95 patients who discontinued TKI in this study received frontline or thereafter third generation TKI.…”
Section: Resultsmentioning
confidence: 99%